2020
DOI: 10.1177/0967391120968432
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of process variables for tensile properties of bagasse fiber-reinforced composites using response surface methodology

Abstract: The present study relates to manufacturing, characterization and optimization of bagasse fiber reinforced composites. For this purpose, response surface methodology was applied to simultaneously optimize the tensile strength, tensile modulus and tensile strain of bagasse fiber reinforced composites. Three levels of process variables, including concentration of sodium hydroxide for bagasse fiber treatment (4, 6, and 8%), content of bagasse fiber (10, 20, and 30 wt%), and length of bagasse fiber (1, 2, and 3 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The percentage errors between the actual and predicted values were 1.12%, 1.87%, 1.39%, and 2.72% for PLA/clay composites loaded with NaOH-modified K85 rice husks, Mg(OH) 2 -modified K85 rice husks, NaOH-modified K98 rice husks, and Mg(OH) 2 -modified K98 rice husks respectively. This suggested that the models' adequacies were reasonable and hence validity was confirmed [35,46,63]. Additionally, the results obtained in each set of composites…”
Section: Process Optimizationsupporting
confidence: 54%
“…The percentage errors between the actual and predicted values were 1.12%, 1.87%, 1.39%, and 2.72% for PLA/clay composites loaded with NaOH-modified K85 rice husks, Mg(OH) 2 -modified K85 rice husks, NaOH-modified K98 rice husks, and Mg(OH) 2 -modified K98 rice husks respectively. This suggested that the models' adequacies were reasonable and hence validity was confirmed [35,46,63]. Additionally, the results obtained in each set of composites…”
Section: Process Optimizationsupporting
confidence: 54%
“…. , t j n (5) where m denotes the quantity of interpolation points (here, m = k + 1), n describes the number of dimensions, f t j 1 , t j 2 , . .…”
Section: Chebyshev Polynomial Fittingmentioning
confidence: 99%
“…Ghasemi et al [ 3 , 4 ] applied the RSM to predict and optimize the tensile strength of polypropylene-based nanocomposites. Siddique et al [ 5 ] examined the impact of process variables on the tensile properties of fiber-reinforced composites using the RSM. The Box–Behnken design in the RSM is used as a DOE method to conduct the modeling process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation